Studi Cost Benefit Analysis di Kolam Renang Ranca Tales Mini Waterboom - Putra, Mohammad Alam Adeyaka; Fahrezi, Muhammad Akmal; Sudianto, Toto (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
In this study, the economic feasibility of the 10% discount promotion on weekdays during the off-season at Ranca Tales Mini Waterboom Swimming Pool in Serang City was assessed. Cost-benefit analysis (CBA) was used as the quantitative approach, and data were obtained through documentation, interviews, and observation. Results showed a 40% increase in the number of visitors; in three months, revenue increased from Rp13,200,000 to Rp17,820,000, with promotional costs of Rp1,800,000 deducted, which resulted in a net benefit of Rp2,820,000 and a Benefit-Cost Ratio (BCR) value of 2.57. In addition to increasing financial returns, this strategy increases customer loyalty, employee motivation, and company competitiveness. As a result, a similar promotion is recommended for the next quiet period.